Peran Media Digital dalam Meningkatkan Pemahaman Siswa pada Pembelajaran Pendidikan Agama Kristen di Indonesia (Jurnal Pendidikan Agama dan Teologi, 2025)
The development of information technology, especially digital media, has had a significant impact on various aspects of life, including education. In the context of Christian Religious Education (PAK) learning in Indonesia, digital media plays an important role in increasing students' understanding. The use of digital media in learning allows students to access richer and more varied sources of information, making it easier for them to understand Christian religious concepts in more depth. Apart from that, digital media can also be used to develop critical thinking skills and enrich students' learning experiences. This research aims to explore the role of digital media in increasing students' understanding of Christian Religious Education learning, as well as to identify the benefits and challenges faced in its implementation in Christian schools in Indonesia. By using a qualitative approach, this research provides insight into how digital media can be used effectively to support a Christian Religious Education learning process that is more interactive and relevant to current developments.